2016
DOI: 10.1097/gox.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Open Capsulotomy: An Effective but Overlooked Treatment for Capsular Contracture after Breast Augmentation

Abstract: Background:The prevailing theory for capsular contracture after breast augmentation is a subclinical capsular infection. A capsulectomy, site change, and implant replacement are recommended. An open capsulotomy leaves the capsule in the patient. Theoretically, such a procedure would be ineffective because it does not remove the infected tissue. Recurrences occurred frequently in women treated in the 1970s when leaky silicone gel implants were in use. Open capsulotomy has not been studied in women implanted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 82 publications
0
55
0
Order By: Relevance
“…Subglandular implant placement is shown to have increased rates of capsular contracture. 33 In both groups A and B for this study, more implants were placed in submuscular pockets (65% and 93% for groups A and B, respectively). Only 1 of the capsular contracture in group A resulted from subglandular placement, whereas none of the reported capsular contractures for group B resulted from subglandular implant placement.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Subglandular implant placement is shown to have increased rates of capsular contracture. 33 In both groups A and B for this study, more implants were placed in submuscular pockets (65% and 93% for groups A and B, respectively). Only 1 of the capsular contracture in group A resulted from subglandular placement, whereas none of the reported capsular contractures for group B resulted from subglandular implant placement.…”
Section: Discussionmentioning
confidence: 88%
“…In a larger study, it was reported that 36% of contractures that will occur within 10 years, will occur in the first 12 months, and that 65% will occur within the first 4 years. 32 , 33 Of the total 166 patients included in this study, 93 patients (56%) were 4 or more years postoperative at the conclusion of data acquisition and follow-up. All the capsular contractures in group A occurred within 4 years of implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons performed open capsulotomy, which does not remove the capsule from the body and reinserts the intact implant, more often in the past. A retrospective study suggests that an open capsulotomy is a safe treatment and there is no significant difference between capsulectomy and open capsulotomy in the CC recurrence rate [45]. However, this study consists of small sample size and does not provide adequate evidence.…”
Section: Management Approaches To CCmentioning
confidence: 87%
“…However, there is little scientific justification for these preferences. 42 Although a recent historical-control multi-site retrospective study 43 concludes that a Keller funnel (Keller Medical, Stuart, Fla.) reduces the capsular contracture rate, there were confounding variables and a short (12-month) follow-up period.…”
Section: Discussionmentioning
confidence: 99%